Order-by-disorder from bond-dependent exchange and intensity signature of nodal quasiparticles in a honeycomb cobaltate - M. Elliot (Nature Portfolio, 2021)
It was suggested that some 3d materials display bond-dependent exchange interactions, leading to exotic many-body effects. Here, using inelastic neutron scattering, the authors reveal such interactions in the stacked honeycomb magnet CoTiO3 and show how they induce a spectral gap and affect the Dirac magnon band structure.